INTERNATIONAL INTELLECTUAL PROPERTY LAW: A STUDY ON ‘GYRINOPS WALLA - Hirimburegama, Yasith Kumara (PEOPLE: International Journal of Social Sciences, 2015)
Pointing out the necessary loopholes and gaps in the local legal system to protect Intellectual Rights and challenges in the legal system. Intellectual Property Right is to protect intangible property of the owners. Sometimes Industrialized countries to manipulate the resources available in developing countries use this concept as a tool. Further, there are other challenges such of lack of technology to exploit resources for developing countries. A method must be introducing vis-à-vis the protection of Traditional Knowledge and at the same time it must pave a way to the benefit of the society by exploiting the knowledge.